PENGARUH MANAJEMEN MODAL KERJA DAN LIKUIDITAS TERHADAP PROFITABILITAS - Hilham Ash Shiddigie; Sugeng Priyanto (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2021)
The aims of this research is to recognize the effect of working capital turnover, receivable turnover, inventory turnover, and liquidity that are proxied at the current ratio of companies incorporated in 27 business index of Indonesia Stock Exchange for the period 2013-2017. The sampling technique used a purposive sampling method and based on predefined criteria has obtained a sample of 10 companies from the total population of 27 companies incorporated in 27 business index on the Indonesia Stock Exchange. The tool that used in this research is multiple linear regression analysis tested by using the statistical package for the social sciences (SPSS) version 25.0. The data that used during the research period is secondary data in the form of complete financial statements. The results of this research showed that the variable of inventory turnover, and liquidity have a positive effect and significant effect on profitability, meanwhile the working capital turnover, and account receivable turnover did not affect profitability. Keywords: Working Capital Turnover, Receivable Turnover, Inventory Turnover, Likuiditas and Profitability